AGAMA DAN KOMUNITAS VIRTUAL: STUDI PERGESERAN ORIENTASI KEAGAMAAN DI ERA DIGITAL - Hablun Ilham (Kopertais Wilayah III Yogyakarta, 2022)
Technological developments have changed the social and religious structure of society from being conventional or traditional to being digital. This paper aims to see how the dynamics of religion in the digital era, in this case the shift in religious orientation from absolute truth to shared cultural wealth, starting from the concept of religion and virtual communities to shifts in religious orientation in the digital era. This research is based on library research by making books or journal articles as primary data. The results showed that the development of technology changed the structure and diversity of society. This can be seen from the emergence of online or virtual based communities such as online churches to online boarding schools. Besides that, Religion in the digital global era experiences a shift in the orientation of religious understanding. This can be seen from the celebrations of religious holidays which are no longer carried out by adherents of that religion. However, nowadays religious activities or especially the celebration of certain religious holidays such as Christian Christmas, for example, are also carried out by people from non-Christian circles. In this context then religion is no longer understood as something rigid or absolute that only certain religions have, but nowadays religion has become a shared cultural property. Research related to religion in the digital era needs to be developed with more religious methods and approaches. This is done to identify problems that have not been identified. Keywords: Religion, the Digital Age, Shifts in the Orientation of Religious Understanding.